Smart Virtual Reality–Artificial Intelligence for Improving Vulva Hygiene Knowledge and Attitudes among Early Adolescents Girls: Smart VR-AI untuk Meningkatkan Pengetahuan dan Sikap Remaja Awal Mengenai Kebersihan Vulva - Rizkia Sukma Nurhaliza; Lisna Anisa Fitriana; Asih Purwandari Wahyoe Puspita (Universitas Pelita Harapan, 2025)
Vulva hygiene is a crucial yet often overlooked aspect of adolescent reproductive health, and early adolescents often lack engaging and effective educational media. Smart Virtual Reality–Artificial Intelligence (VR–AI) based education provides an immersive and personalized learning experience, which has the potential to improve health literacy more effectively than conventional approaches. This study aimed to evaluate the effectiveness of VR–AI–based education in improving knowledge and attitudes related to vulva hygiene among early adolescent girls. A quasi-experimental nonequivalent pretest–posttest control group design was conducted at a public elementary school in Purwakarta, Indonesia, involving 35 female students aged 10–13 years, divided into intervention (n=18) and control (n=17) groups. The intervention group received a 3-minute VR–AI educational video via VR headsets, while the control group received a conventional lecture with equivalent duration and content. Knowledge and attitudes were measured using validated questionnaires and analyzed with parametric and nonparametric tests at a significance level of α=0.05. Both groups experienced significant improvements in knowledge (intervention: p<0.001; control: p=0.003) and attitudes (intervention: p=0.001; control: p=0.010). Post-test attitudes were significantly higher in the intervention group compared with the control group (p=0.014), although knowledge did not differ significantly (p=0.075). VR–AI–based education enhances positive attitudes and represents a beneficial approach to adolescent reproductive health promotion. Schools are encouraged to integrate VR–AI media as a complementary strategy to strengthen the effectiveness and long-term sustainability of health education programs.